2019
DOI: 10.1021/jacs.9b09414
|View full text |Cite
|
Sign up to set email alerts
|

Counting the Number of Glutamate Molecules in Single Synaptic Vesicles

Abstract: Analytical tools for quantitative measurements of glutamate, the principal excitatory neurotransmitter in the brain, are lacking. Here, we introduce a new enzyme-based amperometric sensor technique for the counting of glutamate molecules stored inside single synaptic vesicles. In this method, an ultra-fast enzyme-based glutamate sensor is placed into a solution of isolated synaptic vesicles, which stochastically rupture at the sensor surface in a potential-dependent manner at a constant negative potential. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 32 publications
2
43
1
Order By: Relevance
“…Our finding of small but regular synaptic cross-talk violates modelling studies which predict that cross-talk at AMPA-Rs is negligible and at NMDA-Rs at least two-fold smaller than what we observe experimentally [11,[15][16][17][18]. To some degree this difference could be explained by more recent estimates of certain biological parameters such as a higher glutamate content of synaptic vesicles (7000-8000 molecules) [56,57], a wider synaptic cleft (>=24 nm) [72][73][74] and a deeper understanding of glutamate transporter reaction schemes [75]. A further shortcoming of existing modelling studies may be the approaches used to approximate diffusible signaling on the nanoscale in the brain.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…Our finding of small but regular synaptic cross-talk violates modelling studies which predict that cross-talk at AMPA-Rs is negligible and at NMDA-Rs at least two-fold smaller than what we observe experimentally [11,[15][16][17][18]. To some degree this difference could be explained by more recent estimates of certain biological parameters such as a higher glutamate content of synaptic vesicles (7000-8000 molecules) [56,57], a wider synaptic cleft (>=24 nm) [72][73][74] and a deeper understanding of glutamate transporter reaction schemes [75]. A further shortcoming of existing modelling studies may be the approaches used to approximate diffusible signaling on the nanoscale in the brain.…”
Section: Discussioncontrasting
confidence: 91%
“…The number n of glutamate molecules released by our uncaging pulse can then be estimated by: n = 0.2 fl * 5 mM * ε * ExVF * NAv ~ 36000, with ExVF being the extracellular volume fraction (0.2) and ε the estimated fraction of glutamate uncaged (0.3, see discussion). Assuming recent estimates for the number of glutamate molecules per synaptic vesicle, ~7000-8000 [56,57], this calculation shows that our uncaging releases approximately the same number of glutamate molecules contained in 5 synaptic vesicles. We combined those estimates and calculated the approximate glutamate concentration profile around the uncaging position and superimposed it on an electron micrograph of a cortical synapse for a rough spatial comparison (Fig.…”
Section: Resultsmentioning
confidence: 71%
“…Glutamate concentrations in the synapse can range from less than 20 nM to 5 mM and a recent study found that glutamate concentration in isolated synaptic vesicles was approximately 700 mM [ 13 , 14 , 15 ]. Glutamate binds to three ionotropic receptors (i.e., N -methyl- d -aspartate (NMDA), α-amino-3-hydroxy-5-methyl-4-isoxazoleproprionic acid (AMPA), and kainate receptors), which are all channels that allow the passage of Na + , K + and sometimes Ca 2+ .…”
Section: Amino Acidsmentioning
confidence: 99%
“…If these experiments are representative, it is very likely that many transmitters are released by partial release. Preliminary evidence with a glutamate biosensor suggests partial release might occur for this transmitter as well [48] . The number of glutamate molecules in an isolated vesicle of rodent brain was about 8 000, while only 5 200 molecules were released during exocytosis, resulting in 65 % fraction of glutamate release; however, control experiments blocking glutamate and without glutamate dehydrogenase are needed to give confidence that glutamate is indeed being measured in these experiments, leaving this still as an area to explore and verify.…”
Section: Discussionmentioning
confidence: 99%